(3GdTaGAs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3jHJOF HGNJUGQ GdebGdI GdChdi ef CbdjOS Hbhdg GdfbWI gi TF eG dG LRA dg, hGdNW Whd HdG YQV hWQaGg fbWJGf CdN s
(3BNQgG (B:s
(3jfJgi HBNQ GdebGdI GdNGeSI YTQ hJe HJeGegG eNJUQ GbdjOS, hgPG BNQ GdLRA GdJGSY YTQ ef cJGH GdTaG s
(3GdbSe GdQjGVis
(3GdfSNI HgG MhGTs
(3fSNI QGHYI YTQs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs